Analysis of Leachate Generation Dynamics in a Closed Municipal Solid Waste Landfill by Means of Geophysical Data (DC Resistivity and Self-Potential Methods) - Helene, Lívia Portes Innocenti; Moreira, César Augusto [UNESP] (Springer Nature, 2021)
The degradation of MSW in landfills occurs naturally from the beginning of the disposal, during landfill operation and even after its closure, over a period of several years. The monitoring of closed landfills can be quite costly when done only by direct methods, especially in areas where technical and financial resources are restricted. This work presents a case study in the extreme south of Brazil that represents the vast majority of landfills in the country: public landfills, in small ditches with little resources. The geophysical survey sought to identify leachate accumulation zones and verify their chemical stability in relation to the geological environment from the joint analysis of the electrical resistivity and self-potential data. Data acquisition took place on the same date (02/2018), with results that reveal leachate generation areas (−60 mV and ~ 30 Ωm), leachate accumulation (−40 mV and ~ 20 Ωm) and areas with a predominance of inert waste (> 40 mV), where previously existing organic matter was practically degraded. The combined use of geoelectric methods to understand the degradation dynamics of organic matter in landfills allows for the recognition of active zones of leachate generation, information that supports chemical stabilization projects and site remediation.
Keywords: degradation; electric resistivity; Landfill; leachate; natural electric potential; organic matter